The Relationship between Level of Knowledge and Attitude toward Diet to Prevent Iron Deficiency Anemia among Female Students at SMAN 1 Kuaro - Novia Erfina Dwi Amini (ITKES Wiyata Husada Samarinda, 2021)
Iron deficiency anemia, one of health problems for Indonesian society, can be experienced by all age groups started from children aged under five years old until elderly people. Female adolescents are prone to be iron deficiency anemia due to menstrual blood loss. They will also be at risk for anemia during their pregnancy. This condition negatively impacts on the development and growth of a fetus, or it even causes maternal and fetal death. This study aims to find the relationship between level of knowledge and attitude toward diet to prevent iron deficiency anemia among female students. The design of this study was cross sectional. Systematic Random Sampling as the sampling technique was used to select 127 female students. The findings revealed that the majority of female students at SMAN 1 Kuaro had good level of knowledge toward anemia (52,0%) with p = 0,950 and good attitude toward anemia (76,4%). However, the majority of participants showed poor diet in their efforts to prevent iron deficiency anemia (85,0%). In conclusion, there is no significant relationship between level of knowledge and attitude toward diet to prevent iron deficiency anemia.